Empowering employees through the performance appraisal process - Kennedy, Jeffrey C. (1995)
This article describes how performance appraisal can be used to assist in empowering employees, using as an example the Corporate Finance Office of the New Zealand Department of Social Welfare. Increasing demands are being placed on many public servants as civil service organizations seek to increase productivity and operate with fewer levels of management. Moves away from traditional bureaucratic organization structures are often accompanied by attempts to develop a more empowering culture. These typically involve leadership initiatives adapted from the private sector in areas such as vision, values, participation and trust. One of the most important of these is the performance appraisal system
Keywords: Public Administration - New Zealand; Personnel Management - New Zealand; Employees - Rating of - New Zealand